Effect of vaginal douching on vaginal flora and genital infection - Yıldırım, Rasime; Vural, Gülşen; Koçoğlu, Esra (Galenos Yayinevi, 2020)
This study aimed at examining the effect of vaginal douching (VD), which is a traditional and cultural application, on the vaginal flora and genital infections.This descriptive study included 190 women including those who did or did not perform VD. A questionnaire survey and vaginal sampling were employed. The collected samples were transported within 8 h for laboratory testing.There was no significant difference between the two groups in terms of vaginal flora. In the VD group, only a few patients reported a history of Sexually Transmitted disease (STD), but none in the non-VD group had STDs (p<0.05). No significant difference in infections was noted. However, there was a significant relationship between the history of infections and VD (p<0.01).Women who performed VD are at risk for vaginal infections. Further studies are warranted in the future for clinical application.
Keywords: Original Investigation; 3. Good health